História natural de Phyllomedusa ayeaye (Anura, Hylidae) na Serra da Canastra, Minas Gerais - Borges, Marília Merli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
A total of 988 species of anuran amphibians are currently known for Brazil. Amphibians are among the most threatened groups nowadays, mostly due to loss and alteration of habitats and diseases. This study describes the natural history of Phyllomedusa ayeaye (Anura: Hylidae) and was conducted in the Brazilian Cerrado, probably the most threatened savanna in the world. The studied stream is located in the Serra Canastra mountain range, Minas Gerais state. Field expeditions were conducted monthly from October 2013 to March 2014 and sporadic observations made in December 2010, January 2011, February 2011, April to June 2011, and December 2014 were considered here. Species' reproductive pattern was intermediate between explosive and prolonged, amplexus was axillary, and the species exhibited the reproductive mode typical for the genus. The number of males calling was significantly correlated with air temperature. From 41 males sampled, we recaptured 14 individuals from one to four times, totalizing 24 recaptures in a time interval of 13 months and a maximum displacement of 40 meters. There was no significant difference in body size between males captured just once and recaptured males. Males called from a variety of calling substrates along a temporary stream, mainly from shrubs of Leandra sp. (Melastomataceae). Females were significantly larger than males. Clutches were found on folded leaves of Leandra sp., containing yellowish eggs with eggless gelatinous capsules. Mean eggs per clutch was 29 ± 2.38 (N = 6) and mean egg diameter was 2.84 ± 0.02 mm (N = 109). The reproductive investment (gonad mass/body mass*100) of females was 4.25 ± 0.35% (N = 3) and that of males was 0.16 ± 0.05% (N = 14). Aggressive behaviors including fights and aggressive calls were registered. Males emitted two types of advertisement calls: a simple call, composed by a sequence of short notes and a composite call, with a sequence of short notes followed by a long ...

No Brasil, até hoje foram descritas 988 espécies de anfíbios anuros. O grupo dos anfíbios é um dos mais ameaçados atualmente, principalmente devido à perda e modificação de habitats e doenças. Este estudo sobre a história natural de Phyllomedusa ayeaye (Anura: Hylidae) foi conduzido no Cerrado brasileiro, provavelmente a savana mais ameaçada do mundo. O riacho estudado está localizado na Serra da Canastra, Estado de Minas Gerais. Foram realizadas expedições mensais de outubro de 2013 à março de 2014 e foram incorporadas observações realizadas em dezembro de 2010, janeiro e fevereiro de 2011, abril à junho de 2011 e dezembro de 2014. Phyllomedusa ayeaye apresentou padrão reprodutivo intermediário entre explosivo e prolongado, amplexo do tipo axilar e modo reprodutivo típico do gênero. O número de machos cantando teve correlação positiva significativa com a temperatura do ar. Dos 41 machos amostrados, 14 foram recapturados entre uma e quatro vezes, totalizando 24 recapturas com um intervalo de tempo de até 13 mesese deslocamento máximo de 40 metros. Não houve diferença significativa no tamanho do corpo de machos capturados uma única vez e machos recapturados. Os machos cantaram sobre diversos substratos ao longo de um riacho temporário, principalmente sobre arbustos de Leandra sp. (Melastomataceae). As fêmeas foram significativamente maiores que os machos. As desovas foram encontradas em folhas dobradas de Leandra sp., contendo ovos amarelados e muitas cápsulas gelatinosas sem ovos. A média do N de ovos/desova foi de 29 ± 2,38 (N = 6) e a média do diâmetro dos ovos foi de 2,84 ± 0,02 mm (N = 109). O investimento reprodutivo (massa gônada/massa corpo*100) das fêmeas foi de 4,25 ± 0,35% (N = 3) e dos machos de 0,35 ± 0,05% (N = 14). Comportamentos agressivos incluindo de brigas e vocalizações foram registrados. Machos emitiram dois tipos de canto de anúncio, um canto simples, composto por uma sequência...
Keywords: Anura; Anuro; Herpetologia; Reprodução; Bioacustica; Historia natural; Cerrados; Parque Nacional da Serra da Canastra (MG)